TELUSUR SEJARAH MOTIF BATIK PADA LOMAR BADUY - Tety Suparti; Khoirul Umam (SENDIKRAF Jurnal Pendidikan Seni dan Industri Kreatif, 2023)
This research aims to investigate the history of batik motifs applied to the head band, or "lomar,"of the Baduy community and the batik tradition among the Sundanese people, particularly in theBanten region. A descriptive-qualitative method was used, with data collection through literaturereviews, documentation, and interviews. The research findings indicate that the Sundanese peoplehave a tradition of batik making, as documented in ancient Sundanese manuscripts. The study alsofound that batik has been circulating in Baduy since the 1960s, although customary rules prohibitproducts from outside their ancestral land. One of the pioneers in selling batik in Baduy, AyahNasirah, initiated the production by ordering batik from batik craftsmen in Karet, Jakarta. Due tobusiness competition, a Baduy resident brought it to a Chinese businessman in Rangkasbitung andlater mass-produced it in Pekalongan. Based on documentary studies, in the 1950s and 1960s, themotif of hariang or tapak kebo began to be applied to head bands worn by several Baduyindividuals, although it was not as uniform as it is today. Until now, it is still unknown who initiatedthe production and the intellectual property rights to the motifs on the Baduy head bands, or lomar.In conclusion, the indigenous Baduy community does not produce batik. The batiks circulating andbeing applied to lomar head bands and cloth "lunas" are commissioned from batik producers inPekalongan. In other words, Baduy is both the "brand name" and the "market" for batik productsthat are not produced in their customary territory. Nevertheless, the hariang and tapak kebo motifs,as well as other batik motifs that continue to emerge to this day, acknowledged or not, have becomethe identity of the Baduy indigenous community. Tujuan penelitian ini adalah untuk menyelidiki sejarah motif batik yang diaplikasikan pada ikatkepala atau "lomar" Baduy dan terkait tradisi membatik di kalangan masyarakat Sunda, khususnyadi wilayah Banten. Metode kualitatif deskriptif digunakan dengan pengumpulan data menggunakan literatur, dokumentasi, dan wawancara. Hasil penelitian menunjukkan bahwa masyarakat Sundamemiliki tradisi membatik, seperti yang terdapat dalam naskah Sunda kuno, Saṅ Hyaṅ SiksaKandaṅ Karəsian. Penelitian juga menemukan bahwa batik telah beredar di Baduy sejak tahun1960-an, meskipun aturan adat melarang produk-produk yang berasal dari luar tanah ulayat.Berdasarkan studi dokumentasi pada tahun 1950—1960-an, motif hariang atau tapak kebo mulaiterlihat diaplikasikan pada ikat kepala yang dipakai oleh beberapa orang Baduy, meskipun belumseragam seperti saat ini. Dari penelitian yang telah dilakukan, dapat disimpulkan bahwa masyarakatadat Baduy tidak membuat batik. Batik yang beredar dan diaplikasikan baik pada ikat kepala(lomar) maupun kain lunas, merupakan hasil pesanan dari produsen batik di Pekalongan. Dengankata lain, Baduy merupakan jenama sekaligus ‘pasar’ dari produk batik yang tidak diproduksi diwilayah adat mereka. Meskipun demikian, motif hariang dan tapak kebo serta motif batik lainnyayang terus bermunculan hingga saat ini, diakui atau tidak, telah menjadi identitas masyarakat adatBaduy.